Hubungan Luas Lesi Radiografi Toraks Berdasarkan Sistem Skoring RALE dengan Derajat Klinis Pasien Covid-19 di RS Universitas Andalas Padang - Annisa Dhea Mutiara; Dewi Nadia Purnama; Septiana Vina Tri (Jurnal Ilmiah Manusia Dan Kesehatan, 2022)
COVID-19 is a contagious infectious disease caused by a highly contagious coronavirus. The RT-PCR method is still used as the gold standard for diagnosing COVID-19, but this examination has several limitations, including delays in the release of examination results, causing delays in diagnosis. A chest radiograph can be performed while waiting for the RT-PCR results to come out. The RALE scoring system on chest radiographs can be used as an easy-to-apply method to assess and triage patients diagnosed with COVID-19. To determine the correlation between chest radiographic lesion based on RALE scoring system with clinical severity of COVID-19 patients at RS Universitas Andalas Padang. This research is observational analytic with a cross sectional design. The Population in the study were patients diagnosed with COVID-19 who underwent chest radiography examinations at the Andalas University Hospital, Padang with a total of 124 samples using the consecutive sampling technique. The most gender were women, namely 71 people (57.3%), the most age was 46-55 years, namely 29 people (23.4%), the most comorbids were having comorbidities, namely 72 people (58.1%) with the type the most disease was hypertension, namely 31 people (25.0%), the most clinical degree was mild, namely 78 people (62.9%), the most extensive chest radiographic lesions were normal, namely 89 people (71.8%), the correlation between chest radiographic lesions with the clinical severity of COVID-19 patients at RS Universitas Andalas Padang, obtained p value = 0.000 with r value = 0.50. The correlation between chest radiographic lesions based on the RALE scoring system and the clinical degree of COVID-19 patients has sufficient correlation strength.